Electron Properties of Baicalein and its Derivatives via Quantum Chemistry Calculation: The Effect of Hydroxyl-substitution at A and C Rings - Li, Xiong (Letters in Organic Chemistry, 2024)
The electron properties of baicalein-family are of great importance in influencing its properties and corresponding bioactivities. In this work, we conducted comprehensive quantum chemistry calculations on pristine baicalein, and its two hydroxyl-substituted derivatives where the hydroxylsubstitution respectively occur at A and C rings. By contrasting with each other, the effects of the hydroxyl-substitution on the electron properties were studied from the aspects of the density of states, molecular orbital, electronic excitation, electrostatic potential, and electron delocalization. According to our computation, the hydroxyl-substitution results in variations in geometry and the consequent electron properties among the discussed molecules. Certainly, this research can contribute to the development of the research on the electron involved properties and the structure-property-activity relationship for the baicalein-family.
Keywords: phenolic compounds